KESADARAN METAKOGNITIF DALAM MENULIS TEKS PROSEDUR SISWA KELAS XI FASE F SMKN 1 SOLOK SELATAN - Sartika Ningsih; Dina Ramadhanti; Sri Mulyani Rusli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Metacognitive knowledge is an important aspect that can help students achieve success in writing. Success in writing is greatly influenced by metacognitive knowledge bases such as personal, task, and strategy. Therefore, this study aims to determine students' metacognitive awareness in writing procedural texts of grade XI Phase F students of SMKN 1 Solok Selatan. This type of research is quantitative with descriptive methods. The sample in this study was 95 grade XI students at SMKN 1 Solok Selatan. Data collection was carried out using questionnaires and interviews. Data analysis was carried out in two ways, namely descriptive analysis for questionnaire data and content analysis for interview results. The results of this study show two things, namely: First, the level of metacognitive awareness and metacognitive strategies in writing procedural texts of students is classified as very high with a percentage of 80.78%. In terms of increasing awareness, students have knowledge that is classified as high with a percentage of 74.63%. In terms of monitoring and evaluation which is classified as very high with a percentage of 85.28%, and in terms of control and regulation it is also classified as very high with a percentage of 82.43%. Second, the metacognitive strategies used by students in writing involve several stages: planning, which involves selecting a topic, understanding the concept of the material, and gathering relevant information. The next stage is development, which involves developing ideas and identifying any obstacles encountered. Finally, evaluation involves summarizing the text to ensure it adheres to linguistic rules and structure. Keywords: Metacognitive Awareness, Writing, Procedural Text